2017
DOI: 10.24843/jiab.2016.v11.i02.p02
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kondisi Keuangan Perusahaan, Kualitas Audit dan Opinion Shopping Terhadap Penerimaan Opini Going Concern

Abstract: This study aims to examine the effect of the company’s financial condition, the audit quality and shopping opinion towards the acceptance of going concern audit opinion. The samples used in this research are manufacturing companies listed in Indonesia Stock Exchange in 2012-2014. The population of this study is132. The samples used are 28 companies selected by random sampling method during the observation period of 3 (three) years. Data was analyzed using logistic regression analysis model. The results show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
27

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 4 publications
1
8
0
27
Order By: Relevance
“…Cognitive dissonance is specifically interpreted as the existence of inconsistencies between behavior and attitudes so that this theory can make it easier to make predictions about individual behavior changes from his attitude. (Rahim, 2016) explained that the agent as the manager of the company will make various efforts to avoid the risk of dismissals relating to the picture of financial statements that are worse.…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…Cognitive dissonance is specifically interpreted as the existence of inconsistencies between behavior and attitudes so that this theory can make it easier to make predictions about individual behavior changes from his attitude. (Rahim, 2016) explained that the agent as the manager of the company will make various efforts to avoid the risk of dismissals relating to the picture of financial statements that are worse.…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…For example Arsianto and Rahardjo (2013) found that audit of tenure had a significant effect on the going concern audit opinions, while Rakatenda and Putra (2016) failed to support the influence this factor. Tjahjani and Novianti (2014), Irwansyah, Oktavianti, and Hardayanti (2015) and Rahim (2016) also show that firms' financial condition stated was a significant factor to the going concern audit opinions, while Wulandari (2014) stated this driver was not significant. Furthermore, the leverage factor in Aryantika and Rasmini's research (2015) was a significant to the going concern audit opinions, the leverage was not important according to Wulandari (2014) and Rakatenda and Putra (2016).…”
Section: Introductionmentioning
confidence: 99%
“…Menurut Wibisono (2011) menjelaskan bahwa financial distress adalah kesulitan keuangan yang dihadapi dalam mempertahankan keberlangsungan usaha di masa mendatang yang mungkin mengawali terjadinya kebangkrutan. Rahim (2016) menegaskan bahwa kesulitan keuangan yang dihadapi perusahaan inilah yang berpotensi diberikan opini audit going concern oleh auditor. Meskipun demikian ternyata tidak sedikit perusahaan yang go public memperoleh opini audit going concern.…”
Section: Pendahuluanunclassified
“…Fanny & Saputra (2005) dan Setyarno et al (2006) menemukan bukti bahwa jika kondisi perusahaan dengan kondisi kinerja keuangan yang baik maka kemungkinan kecil perusahaan tersebut akan mendapat opini going concern dari auditor. Hasil penelitian ini sejalan dengan Rahim (2016) ketika suatu perusahaan mengalami permasalahan keuangan (financial distress), maka kegiatan operational perusahaan akan terganggu yang akhirnya dapat berdampak pada tingginya risiko yang dihadapi perusahaan dalam mempertahankan kelangsungan usahanya dimasa mendatang, menyebabkan berpengaruh pada opini audit yang akan diberikan oleh auditor. Hal ini bertentangan dengan penelitian Januarti (2009) dan Adriana et al (2012) bahwa financial distress tidak memiliki pengaruh terhadap penerimaan opini audit going concern.…”
Section: Pendahuluanunclassified